Scalable discovery of Linked APIs. (1st January 2013) - Stadtmüller, Steffen; Norton, Barry
A number of approaches bring together the principles and technologies which define Linked Data with those of RESTful services. Services and APIs are thus enriched by, and contribute to, the Web of Data. These approaches, referred to as Linked APIs, use graphic patterns as an intuitive way to describe input and output expectations. To enable agents to discover Linked APIs we propose metrics tailored for a scalable discovery system to measure the degree service descriptions match service templates formulated by an agent. The metrics are based on the used vocabularies in the service descriptions and templates as well as on the containment relation of the employed graph patterns. We introduce a cloud-based implementation of our system in a distributed environment to further address scalability. The results of our evaluation show the positive effects of a distributed computation strategy on the performance of our system.